2022
DOI: 10.1021/acs.energyfuels.1c04088
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Influencing Factors of Supercritical Methane Adsorption in Deep Gas Shale: A Case Study of Marine Wufeng and Longmaxi Formations from the Dongxi Area, Southeastern Sichuan Basin (China)

Abstract: Deep shale reservoirs with burial depths of >3500 m are now the target of gas producing intervals in the Sichuan Basin, China. Due to the in situ high temperatures and pressures, methane in deep shale formations is supercritical, resulting in the inapplicability of some conventional adsorption models. To determine the methane adsorption capacity of deep shale and its influencing factors, different shale lithofacies from the Dongxi area of the southeastern Sichuan Basin are investigated and compared in this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Compared with the LM-2 sample, the WF-1 sample with higher organic matter and silica content exhibits a greater methane adsorption capacity, which is consistent with previous studies on the controlling factors of methane ability in Wufeng−Longmaxi shale. 28,46,47 The adsorbed-phase density of the two shale samples is between 0.27−0.38 g/cm 3 and 0.18−0.36 g/cm 3 at different temperatures, which is below the methane liquid density (0.421 g/ cm 3 ). After absolute adsorption and adsorption phase density (ρ ads ), these data will be used to investigate the supercritical methane adsorption kinetic and thermodynamic characteristics.…”
Section: Supercritical Methane Adsorption Experimentsmentioning
confidence: 89%
“…Compared with the LM-2 sample, the WF-1 sample with higher organic matter and silica content exhibits a greater methane adsorption capacity, which is consistent with previous studies on the controlling factors of methane ability in Wufeng−Longmaxi shale. 28,46,47 The adsorbed-phase density of the two shale samples is between 0.27−0.38 g/cm 3 and 0.18−0.36 g/cm 3 at different temperatures, which is below the methane liquid density (0.421 g/ cm 3 ). After absolute adsorption and adsorption phase density (ρ ads ), these data will be used to investigate the supercritical methane adsorption kinetic and thermodynamic characteristics.…”
Section: Supercritical Methane Adsorption Experimentsmentioning
confidence: 89%
“…After experiencing high-pressure and high-temperature thermal evolution, the OM in Longmaxi formation is at the high-mature and overmature stages with the vitrinite reflectance ( R o ) ranging from 2.20% to 4.20%. In addition, the total organic carbon (TOC) content is in the range 0.46–7.13% with an average of 2.66%, and the porosity is in the range 1.2–10.8% with an average of 3.0%. …”
Section: Experiments Methodsmentioning
confidence: 99%
“…Shale is typically split into two primary zones according to the depth at which it was buried: shallow shale (depths under 3500 m) and deep shale (depths beyond 3500 m) (Ma et al, 2021). Recent years shale gas exploration from deep shale becomes the most quickly expanding trends in onshore unconventional oil/gas exploration in South China (Cai et al, 2021; Jiao et al, 2018; Li et al, 2022; Sun et al, 2021; Wang et al, 2022a; Wang et al, 2022b). Previous workers have focused on reservoir characterization, reservoir property, pore-fracture structure, gas content and development potential of deep shale gas and achieved remarkable success in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Previous workers have focused on reservoir characterization, reservoir property, pore-fracture structure, gas content and development potential of deep shale gas and achieved remarkable success in this field. Wang et al (2022b) proposed a method of estimating the supercritical methane adsorption in deep shale from the Dongxi Area, Southeastern Sichuan Basin. They carried out methane isothermal adsorption experiments at different temperatures (30–90 °C) and pressures (up to 32 MPa), and suggested that the methane adsorption capacity increases with pressure and decreases with temperature.…”
Section: Introductionmentioning
confidence: 99%